Rethinking modernity and national identity in Turkey (Publications on the Near East, 1997)
Kemalist certainties and modern ambiguities /; Resat Kasaba --; Whither the project of modernity? Turkey in the 1990s /; Çaglar Keyder --; Modernization policies and Islamist politics in Turkey /; Haldun Gülalp --; Projects as methodology : some thoughts